Caracterização de padrões de acesso a vídeos em portais de mídia especializada - Lucas Cunha de Oliveira Miranda (2013)
Watching online videos is part of the daily routine of a considerable fraction of Internet users nowadays. We have seen an expansion of more interactive, social and collaborative applications on the Web. Therefore, production and consumption of multimedia content increased significantly in recent years. This increase has occurred mainly in Brazil, which today ranks among the top ten online video markets worldwide. In this context, understanding the patterns of video consumption on the Web is paramount for improving the capacity planning for video providers, the conversion rate for advertisers, and the relevance of the whole online video watching experience for end users. While much research has been conducted to analyze video access patterns in user-generated content (UGC), little is known of how such patterns manifest in mainstream media (MSM) sites. In this work, we perform the first large-scale analysis of video access patterns in MSM portals. As a case study, we analyze interaction logs across a total of 38 Brazilian MSM Websites, including six of the largest portals in the country, over a period of eight weeks. Our analysis revealed interesting static, temporal and transactional video access patterns, which we compare and contrast to the access patterns reported for UGC Websites. Overall, our analysis provides several insights for an improved understanding of video access on the Internet beyond UGC Websites.